Effects of contrast enhanced positron emission tomography/computed tomography in cancer imaging - Mahmud, Mohd Hafizi (2015)
Integrated Positron Emission Tomography/Computed Tomography (PET/CT) with the use of fluorine-18 (18F) isotope tagging with fluorodeoxyglucose (FDG) tracer (18FFDG) is becoming an important tool for clinical investigation with increase clinical utilization particularly in oncology. Application of intravenous (IV) contrast-enhanced CT (CECT) in PET imaging has been reported to lead for overestimation on the standardized uptake value (SUV) of attenuation-corrected PET. The major aim of this study was to investigate the effect of IV contrast-enhanced PET/CT scanning protocol on the CT value and PET SUV at the Centre for Diagnostic Nuclear Imaging of Universiti Putra Malaysia (CDNI UPM) in cancer imaging in view to be recommended as a standard imaging procedure. Whole body 18F-FDG PET/CT scans of 75 oncology cases performed with both non IV contrast-enhanced CT (NECT) and CECT protocols atCDNI UPM for tumour staging were reviewed. The CT value and PET FDG uptake activity as denoted by the mean Hounsfield unit (HUmean) and maximum SUV (SUVmax), respectively of six normal tissues and lesions were quantified using a third party imaging software of OsiriX and compared between the non-contrasted and contrasted PET/CT protocols. The mean SUVmax of all observed lesions was determined and the SUVmax of liver was statistically associated with several biological and procedural related factors. The effective doses resulting from the stand-alone (NECT, CECT and PET) and integrated (summation of NECT, CECT and PET) scanning protocols were calculated by means of the published and modified dose coefficients. Statistical analysis was performed using SPSS with p < 0.05 considered as significant. Statistically significant and insignificant changes were found in HUmean (p < 0.001) and SUVmax values (p >0.05), respectively in all normal tissues and lesions. The mean SUVmax of overall lesions was 9.70 ± 4.19 and 9.71 ± 4.18 for non-contrasted and contrasted lesions, respectively. The SUVmax of the liver was significantly influenced by age, body mass index (BMI), fasting blood glucose level and incubation period (p <0.05) as shown by multiple linear regression analysis. The mean effective doses contributing from CT and PET were 21.13 ± 4.62 mSv and 5.75 ± 0.50 mSv, respectively, resulting in the total whole body PET/CT effective dose of 26.89 ± 4.7 PM ii mSv. A statistically significant difference of effective doses was found among the three stand-alone scanning protocols (p < 0.001). As a conclusion, this study revealed no significant changes in the semiquantification uptake value of attenuation corrected PET as a result of utilization of the IV CECT protocol in PET/CT imaging. The highly cut-off value of SUVmax (9.70 – 9.71) of cancerous lesions was acquired in the CDNI UPM. Age, BMI, fasting blood glucose level and incubation period were significant factors influencing the physiological FDG uptake of the liver. The mean total patient effective radiation dose resulting from the total whole body PET/CT study was 26.89 ± 4.75 mSv. Therefore, contrasted contemporaneous PET/CT protocol canbe usedas a first line tool in routine PET/CT study in selectedoncologycases optimizing the value of this integrated imaging modality for clinical investigation of cancer disease.